2021
DOI: 10.1007/s10943-021-01346-y
|View full text |Cite
|
Sign up to set email alerts
|

Islam and the COVID-19 Pandemic: Between Religious Practice and Health Protection

Abstract: This paper concerns a problem, the global pandemic COVID-19, which has influenced religious practices with respect to health protection across the Muslim world. Rapid transmission of the virus between people has become a serious challenge and a threat to the health protection of many countries. The increase in the incidence of COVID-19 in the Muslim community took place during and after the pilgrimages to Iran's Qom and as a result of the Jamaat Tabligh movement meetings. However, restrictions on religious pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 37 publications
0
30
0
1
Order By: Relevance
“…Research highlights, among other aspects, that religion and spirituality are necessary sources that activate individual coping strategies in order to support individuals in developing life satisfaction [ 39 , 40 ]. Religiousness and the ability for religious coping can be considered as protective factors when individuals struggling with their fears and concerns have an absolute trust in God and when they express patience and gratitude under all circumstances, including those of sorrow and worry [ 32 , 41 , 42 ]. Furthermore, developing deeper religious faith through prayer, reading holy books, and listening to inspirational programs may help individuals stay mentally healthy, as it has been reported that religious practices are associated with less anxiety and stress, as well as with greater hope [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research highlights, among other aspects, that religion and spirituality are necessary sources that activate individual coping strategies in order to support individuals in developing life satisfaction [ 39 , 40 ]. Religiousness and the ability for religious coping can be considered as protective factors when individuals struggling with their fears and concerns have an absolute trust in God and when they express patience and gratitude under all circumstances, including those of sorrow and worry [ 32 , 41 , 42 ]. Furthermore, developing deeper religious faith through prayer, reading holy books, and listening to inspirational programs may help individuals stay mentally healthy, as it has been reported that religious practices are associated with less anxiety and stress, as well as with greater hope [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…For a person who aims to make sense of everything, religion can become a way to find meaning in life, making it easier for a person to establish a cause-and-effect relationship for challenging events, fulfilling such a person’s need for meaning (Yapıcı, 2020 ). Supporting this idea, some researchers have found that the more strongly one adheres to a religion, the lower that person’s acceptance is of pandemic restrictions (Piwko, 2021 ). According to Alport ( 2006 ), religion answers existential questions by offering people meaning and purpose, thus protecting them from anxiety, doubt, and despair.…”
Section: The Role Of Religionmentioning
confidence: 99%
“…Nevertheless, doing so during a pandemic can bolster the spread of COVID-19. Therefore, the mosque as a place where congregational prayers are performed is one of the places most prone to spreading COVID- 19.…”
Section: Introductionmentioning
confidence: 99%
“…The use of protective measures is justified as part of a broader pandemic response strategy [18]. COVID-19 is a highly contagious virus that can be prevented by increasing the frequency and type of preventive measures, as well as the number of activities performed [19]. Therefore, failure to maintain an appropriate protective measure in congregational prayer contributes to the uncontrolled transmission of the virus [20].…”
Section: Introductionmentioning
confidence: 99%